Association of pregnancy with engagement in HIV care among women with HIV in the UK: a cohort study. Issue 12 (December 2021) - Okhai, Hajra; Tariq, Shema; Burns, Fiona; Gilleece, Yvonne; Dhairyawan, Rageshri; Hill, Teresa; Peters, Helen; Thorne, Claire; Sabin, Caroline A; ,; Ainsworth, Jonathan; Allan, Sris; et al.
Summary: Background: Women with HIV face challenges in engaging in HIV care post partum. We aimed to examine changes in engagement in HIV care through clinic attendance before, during, and after pregnancy, compared with matched women with HIV who had never had a recorded pregnancy. Methods: In this cohort study, we describe changes in engagement in HIV care before, during, and after pregnancy among women with HIV from the UK Collaborative HIV Cohort (CHIC) study from 25 HIV clinics in the UK with a livebirth reported to the National Surveillance of HIV in Pregnancy and Childhood between Jan 1, 2000, and Dec 31, 2017. To investigate whether changes were specific to HIV, we compared these changes to those over equivalent periods among non-pregnant women with HIV in the UK CHIC study matched for ethnicity, year of conception, age, CD4 cell count, viral suppression, and antiretroviral therapy use. Analyses were via logistic regression using generalised estimated equations with an interaction between case-control status (pregnant women vs non-pregnant women) and pregnancy or pseudo pregnancy (for non-pregnant women) stage. Findings: 1116 matched pairs of pregnant and non-pregnant women were included (median age 34 years [IQR 30–38], 80·1% Black African, 12·5% white). 69 330 person-months of follow-up were recorded, 25 412 in the before stage, 18 897 during, and 25 021 after pregnancy or pseudo pregnancy stages. Among pregnant women, the proportion of time engaged in care increased during pregnancy (8477 [90·5%] of 9371 person-months) and after pregnancy (10 501 [84·6%] of 12 407), compared with before pregnancy (9979 [78·5%] of 12 707). Among non-pregnant women in the control group, engagement in HIV care remained stable across the three equivalent stages (9688 [76·3%] of 12 705 person-months before pseudo pregnancy; 7463 [78·3%] of 9526 during pseudo pregnancy; and 9892 [78·4%] of 12 614 after pseudo pregnancy). The association of engagement in HIV care with pregnancy or pseudo pregnancy stage differed significantly by case-control status (pinteraction <0·0001); the odds of engagement in HIV care were higher during pregnancy (odds ratio [OR] 3·32, 95% CI 2·68–4·12) and after pregnancy (OR 1·49, 1·24–1·79) only among pregnant women, and not among non-pregnant women, when compared with the before pseudo pregnancy stage. Interpretation: Women with HIV and a pregnancy resulting in a livebirth were more likely to engage in HIV care post partum when compared with before pregnancy. A detailed understanding of the reason for this finding could support interventions to maximise engagement in HIV care for all women with HIV. Funding: Medical Research Council and National Institute for Health Research.